Desempeño laboral y su efecto en la formación profesional de las asistentes administrativas del Gobierno Autónomo Descentralizado Parroquial Rural de Ricaurte del cantón Urdaneta - Soriano Cedeño, Astromelia Efigenia (2022)
In this case study entitled as job performance and its effect on the professional training of administrative assistants of the decentralized autonomous rural parish government of Ricaurte of the Urdaneta canton, which aimed to determine the job performance and its effect on the professional training of administrative assistants, where the assistants have been investigated through surveys to obtain the information that was collected for the solution of the problem, for the realization of this case study the descriptive research method was used, the type of research used in reference to the objective of finding an expanded knowledge of the problem, focusing on the inquiry of solutions and strengthening the discernment for its application, as a conclusion in the study that was developed, it has been possible to determine the work performance and its effect on the professional training of administrative assistants, it has been analyzed that several of the administrative assistants do not have adequate professional training according to what is suggested that requires this workplace; As a recommendation in reference to the administrative assistants who work in this institution, they should be educated and self-educated to improve their professional and personal development, since several of them do not have a professional degree according to the function they perform.